3D model atmospheres of DA white dwarfs - Tremblay, Pier-Emmanuel; Ludwig, Hans-Günter; Steffen, Matthias; Freytag, Bernd (18th European White Dwarf Workshop, 2013)
The spectroscopically determined surface gravities of cool hydrogen-atmosphere DA white dwarfs are significantly higher than the mean value of log g ∼ 8 found for hotter objects with radiative atmospheres (Teff > 13 000 K). It was recently suggested that a problem with the treatment of convective energy transport in the 1D mixing-length theory was the explanation for this high-log g problem. We have now computed a grid of pure-hydrogen 3D model atmospheres with the CO5BOLD code for surface gravities from log g = 7 to 8.5 and effective temperatures from 6 000 to 13 000 K. Over this range, the intensity contrast of the surface granulation pattern, which describes the strength of the 3D effects, is varying significantly. We confirm the result of an earlier investigation that 3D model spectra provide a much better characterization of the mass distribution of cool white dwarfs.